A preliminary dynamic model of success to successfull archetype in government budget competition allocation by using balanced score card-like framework - A H Nasution; A Tontowi; B M Shopa; B Hartono (IPTEK Journal of Proceedings Series, 2018)
The budget allocation of Industry and Cooperative Office (Disperindagkop) is the main technical service agency for the leverage of the development of two Superior Industries (IU) of DIY Province, namely Wood Processing Industry (IKA) and Leather Processing Industry (IKU). Dynamic simulation is an alternative method to predict the growth of IKA and IKU performance and an archetype Success to Successfull (S2S) will be conducted to evaluated the effectiveness of government budget competition allocation. Balanced Score Card (BSC) is used as a framework for developing the dynamic hypothesis of the model. After Causal Loops Diagram (CLD) had been developed, both in existing and improvement stage, the next steps to build preliminary dynamic a simulated running model are transforming CLD into Stock and Flow Diagrams (SFD) until tested to proof validity of the model to represent the real condition  and fisible be used as growth prediction of IKA and IKU for the next 16 years ahead. If model had been prooved valid, the scenario model (policy formulation) will be imposed (as shown in Appendices) to check whether the simulation model will impact on objective of the research.